The 5-Factor Modified Frailty Index Predicts Patient Health Burden Following Surgery for Pituitary Adenomas. (16th November 2020) - Khalafallah, Adham M; Shah, Pavan P; Huq, Sakibul; Jimenez, Adrian; London, Nyall; Hamrahian, Amir; Salvatori, Roberto; Gallia, Gary L; Rowan, Nicholas; Mukherjee, Debraj
Abstract: INTRODUCTION: An increasing focus on value-based care has created the need for predictors of cost-related surgical outcomes such as length of stay (LOS) in neurosurgery. Frailty is known to influence these outcomes, but quantification of frailty is often challenging during routine clinical workflows. The novel 5-factor modified frailty index (mFI-5) is a recently-introduced tool that is leaner than its predecessors, and can be readily applied in the clinic to risk-stratify patients. METHODS: The medical records of all patients undergoing endoscopic endonasal resection of pituitary adenomas at an academic medical center between January 2107 and December 2018 were retrospectively reviewed. Bivariate statistical analyses were conducted using Fisher's exact test, the chi-square test, and the independent samples t-test. Linear regression models were used for multivariate analysis. RESULTS: Of 234 patients, 62 had functioning tumors and 172 had non-functioning tumors. The functioning tumor cohort had a mean age of 44.3 years, was 68% female, and majority Caucasian (74%). The average surgical duration for functioning tumors was 252.8 ± 80.4 minutes, and the average total charges were 38, 194 ± 12, 773. The non-functioning tumor cohort had a higher mean age of 57.3 years ( P < .001) and was majority male (56%) ( P < .001). The average surgical duration and total charges for non-functioning tumors were 209.9 ± 75.3 minutes and 34, 456 ± 10, 888, respectively, both lower than functioning tumors ( P = .002 and P = .028, respectively). On multivariate linear regression, with each one-point increase in mFI-5, total LOS increased by 0.76 days in the whole study cohort ( P < .001), by 1.02 days in Cushing disease ( P = .030), and by 0.70 days in non-functioning tumors ( P < .001). Total charges increased by 4, 689 in the whole cohort ( P < .001), by 9, 965 in Cushing disease ( P = .022), and by 3, 655 in non-functioning tumors ( P < .001) with each one-point increase in mFI-5. CONCLUSION: Frailty, as determined by the mFI-5, is associated with increased length of stay and hospital charges for patients undergoing endoscopic endonasal pituitary surgery. These results suggest that this predictive tool may hold peri-operative value in patient counseling for patients with pituitary adenomas.